Exploring the risk factors and prognosis of transverse myelitis in systemic lupus erythematosus - Minhui Wang; Ziqian Wang; Li Zhang; Jiuliang Zhao; Di Wu; Jing Li; Qian Wang; Jinmei Su; Dong Xu; Shangzhu Zhang; Mengtao Li; Xiaofeng Zeng (SAGE Publishing, 2022)
Purpose: We aimed to describe the clinical characteristics and outcomes of patients with transverse myelitis (TM) as a rare manifestation in systemic lupus erythematosus (SLE) and explore the risk factors and prognosis of SLE-related TM (SLE-TM). Methods: We conducted a retrospective case-control and cohort analysis. All patients with SLE-TM (58 patients) and 232 with SLE without TM, as a control group, were admitted to Peking Union Medical College Hospital between January 1993 and May 2021. Factors associated with the presence of SLE-TM and its prognosis were assessed using logistic regression and Cox proportional hazard models. Results: Multivariate analysis revealed that positive anti-Ro/Sjogren's syndrome A (anti-Ro/ SSA) (<0.01) and increased erythrocyte sedimentation rate (ESR) ( p  < 0.01) were associated with SLE-TM. Regarding prognosis, methylprednisolone (MP) pulse therapy within 2 weeks of onset (adjusted hazard ratio (AHR), 2.12; 95% confidence interval (CI), 1.06-4.23; p  = 0.03) was associated with short-term neurological improvement. An American Spinal Injury Association Impairment Scale (AIS) grades of A, B, or C at onset (AHR, 0.12; 95% CI 0.05-0.28; p  < 0.001) and hypoglycorrhachia (AHR, 0.29; 95% CI, 0.13-0.65; p  < 0.01) were associated with a short-term non-improved outcome. Conclusions: The positive anti-Ro/SSA antibodies and increased ESR may be associated with the presence of SLE-TM. An initial presentation with severe myelitis and hypoglycorrhachia appear to be predictors of a poor neurological outcome. Early steroid pulse therapy may improve the prognosis.